Linking Petrography And Petrophysical Analysis In Carbonate Reservoir Characterization: Case Study In Baturaja Formation Offshore Northwest Java - Natasia, Nanda; Alfadli, Muhammad Kurniawan; Arfiansyah, Kurnia; Hardiyono, Adi; Barkah, Mohamad Nursiyam; Haryanto, Iyan (Journal of Geological Sciences and Applied Geology, 2017)
AbstractLinking geological analysis with petrophysical characterization in complex carbonate reservoir is a chalangging task. Many previous researcher has proofed that depositional facies in carbonate reservoir has very little advantages in reservoir quality due to overprinted with diagenetic facies. The difficulties in characterized the carbonate may rise because one does not include some genetic, geometrical and petrophysical character of the pore space, both geometry and distribution. The aim of this study is to evaluate the reservoir rock typing in carbonate reservoir by comparing rock-fabric descriptions analyzed in thin section with laboratory measurements of porosity, permeability, capillarity, and Archie m values. Methodology employed for this study involved the examination of thin sections and the integration of routine analysis data following lucia’s pore classification scheme. The first step in characterized the petrophysical class is the determination of interparticle porosity by substracting the separate vug porosity from total porosity. The separate vug porosity is estimated in petrographic analysis in 325 thin section samples. Than estimating the value for un cored interval by determining the relationships between total porosity, separate vug porosity and sonic interval transit time. The petrographic analysis to estimating the separate vug porosity is a qualitative way, and so the value is not quantitative, but the trend is still implies the value so the relationships between porosity and sonic log can be quantified. Calibration of pore types to acoustic log response is accomplished by making a detailed log of porosity types described from thin sections and constructing Z-plots of total porosity and transit time from logs and separate-vug porosity from thin sections . The “m” value (lithology exponent or cementation factor) is different from the other terms in the Archie equation in that it is related to rock fabrics, specifically to vuggy porosity. Reservoir characterization by using this scheme has proofed that geological analysis made in detailed thin section can be a helpfull tool since the validation in tested and produced interval shows a verry good relationships. Keywords : Reservoir Characterization, Baturaja Fm., Carbonate, Petrophysics.